ÐŸÐ°Ð¼â€™ÑÑ‚Ñ– Ð„Ð²Ð³ÐµÐ½Ñ–Ñ Ð¤ÐµÐ´Ð¾Ñ€Ð¾Ð²Ð¸Ñ‡Ð° ÐšÐ¾Ð¿Ñ–Ð¹ÐºÐ¸ (03.10.1939 â€“ 08.05.2018) - Problems of Cryobiology and Cryomedicine, Editorial Board (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 191